Public Policy Strategy to Improve the Quality of Education in Makassar City - Zainal, Henni (Pinisi Business Administration Review, 2024)
Improving the quality of education is one of the priorities in the development of Makassar City. This study aims to analyze effective public policy strategies in improving the quality of education in Makassar City. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observations, and analysis of policy documents. The results of the study indicate that efforts to improve the quality of education in Makassar City require collaboration between the government, schools, communities, and the private sector. Policies that include improving the quality of educators, developing educational infrastructure, providing access to information technology, and providing scholarships for outstanding students from underprivileged families are effective strategies to improve the quality of education. This study recommends that the Makassar City government continue to innovate in policy formulation and prioritize a participatory approach to ensure that the policies implemented can meet the needs of all stakeholders. Thus, it is hoped that the quality of education in Makassar City can continue to improve and be able to compete at the national and international levels.